2013
DOI: 10.5539/jas.v5n7p61
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Yield Response of Improved Sweet Potato (Ipomoea batatas (L.) Lam) Varieties to Different Rates of Potassium Fertilizer in Calabar, Nigeria

Abstract: A two-year field study was conducted during the growing seasons of 2007 and 2008 in Calabar, south eastern Nigeria to evaluate the response of two improved sweet potato varieties (TIS 8164 and Ex-Igbariam) to five rates (0, 40, 80, 120 and 160 kg K/ha)of potassium fertilizer. Factorial combinations of the treatments were arranged into a randomized complete block design with three replications. Results showed that Ex-Igbariam was more responsive to K application than TIS8164 as indicated by the production of lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 5 publications
3
20
1
Order By: Relevance
“…This might be due to the variation of genetic makeup of the different sweet potato genotypes. The results obtained from the present study are consistent with the results of Rashid et al (2002) and Uwah et al (2013) who stated that the numbers of storage root plantG 1 were found considerable variation. Farooque and Husain (1973) also showed that the storage roots number plantG 1 varied from 4.70-11 and it depends on the genotypes of sweet potato.…”
Section: Fresh and Dry Weight Of Non-storage Roots (G)supporting
confidence: 83%
See 1 more Smart Citation
“…This might be due to the variation of genetic makeup of the different sweet potato genotypes. The results obtained from the present study are consistent with the results of Rashid et al (2002) and Uwah et al (2013) who stated that the numbers of storage root plantG 1 were found considerable variation. Farooque and Husain (1973) also showed that the storage roots number plantG 1 varied from 4.70-11 and it depends on the genotypes of sweet potato.…”
Section: Fresh and Dry Weight Of Non-storage Roots (G)supporting
confidence: 83%
“…The variation was found among the genotypes both in the genetical and growth characteristics. The agreement of the present study closely related to the findings of Uwah et al (2013) who reported that the length of storage root plantG 1 in two years ranges from 14.4-16.3 cm. Rashid et al (2002) and Farooque and Husain (1973) showed that the length of the storage roots differed among the varieties.…”
Section: Yield and Yield Attributing Characteristicssupporting
confidence: 81%
“…But specific gravity (1.14 g ml -1 ) of tuber is increased with decreased nitrogen level. Graded levels of potassium application is significantly increases tuber yield (19,597 kg ha -1 ) and yield contributes are tuber diameter (5.96 cm), tuber length (17.94 cm), number of tubers per plant (9.0) are recorded in the application of 100 kg K 2 O ha -1 and quality attributes are fresh tuber weight (410.26 g), reducing sugar (0.231 %), non reducing sugars (6.23 %), total sugar (6.46 %), TSS (12.69 %), carbohydrates (17.29 %), protein (8.70 %) and specific gravity (1.12 g ml -1 ) of tuber was found @ 100 kg K 2 O ha -1 over control application (K 0 Uwah et al, (2013).…”
Section: Issn: 2319-7706 Volume 6 Number 5 (2017) Pp 1689-1696mentioning
confidence: 99%
“…Information about incorporation of farmers' knowledge in the production of the crop is necessary. Most of the released sweet potato varieties have been evaluated on research farms Njoku et al 2007;Egbe & Idoko 2009;Uwah et al 2013) where the growth environment is supplemented with irrigation, fertilizers and pest and disease control. This article not only reports on the evaluation of locally bred sweet potato cultivars grown on resource-constrained small-scale farms but also provides information on the plant's physiological responses to growth environment and how it (environment) affects plant growth and yield of sweet potato.…”
Section: Introductionmentioning
confidence: 99%